Library research about trigeminal and glossopharyngeal neuralgia, and glosodinia - Leinen de la Caridad Cartaya Benítez; Yanin Benítez Rodríguez; Rolando Mirot Delgado; Flora Luisa Cartaya Díaz; Leonardo Soca Rodríguez (Medimay, 2023)
Introduction: